2006
DOI: 10.1021/ja060112b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biochemical Evaluation of Phosphonoformate Oligodeoxyribonucleotides

Abstract: Phosphonoformate oligodeoxyribonucleotides were prepared via a solid phase synthesis strategy. The first step in the preparation of appropriate synthons was condensation of bis(N,N-diisopropylamino)phosphine and diphenylmethylsilylethyl chloroformate in the presence of sodium metal to yield formic acid, [bis(N,N-diisopropylamino)phosphino]-beta-(diphenylmethylsilylethyl) ester. The product of this reaction was then condensed with appropriately protected 2'-deoxynucleosides using 4,5-dicyanoimidazole to yield t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 35 publications
(51 reference statements)
0
24
0
Order By: Relevance
“…All three phosphodiester modifications showed very high nuclease resistance when incubated with snake venom phosphodiesterase or DNase I. Phosphonoacetate and thiophosphonoacetate containing oligonucleotides are one of the first examples of chimeras having capped ends with a catalytic PS central region stimulating RNase H1 catalysis at rates faster than native DNA. [2,3] The conformational locking of oligonucleotides has been shown to be favourable for hybridisation with complementary RNA/DNA. Most notable examples include LNA and BNA, which are discussed below.…”
Section: Backbone Modificationsmentioning
confidence: 99%
“…All three phosphodiester modifications showed very high nuclease resistance when incubated with snake venom phosphodiesterase or DNase I. Phosphonoacetate and thiophosphonoacetate containing oligonucleotides are one of the first examples of chimeras having capped ends with a catalytic PS central region stimulating RNase H1 catalysis at rates faster than native DNA. [2,3] The conformational locking of oligonucleotides has been shown to be favourable for hybridisation with complementary RNA/DNA. Most notable examples include LNA and BNA, which are discussed below.…”
Section: Backbone Modificationsmentioning
confidence: 99%
“…However, a minor product with a peak in the 31 P NMR spectrum near 63 ppm was observed that was comparable to that exhibited by 6 at 52 ppm. We repeated Caruthers’ method [ 46 ], which involved a two hour reflux of 4 with sodium, and similarly detected no visible disappearance of the sodium. No reaction of this mixture with acetic anhydride was detected, beyond the occasional appearance of the 63 ppm peak.…”
Section: Resultsmentioning
confidence: 99%
“…While the deoxygenation of phosphine oxides is known [ 44 45 ], deoxygenation of the functionally much more complex phosphonate 3b to the dinucleoside analog of 1 was not attempted. Only one example of an acylphosphonite analog of 1 was found in the literature, namely, a dinucleoside formate reported by Caruthers et al [ 46 ]. As shown in Scheme 1 , the reaction of H -phosphonodiamidite 4 with chloroformate 5 gave acyl diamidite 6 , which by following standard nucleoside coupling protocols gave the formate phosphonite 1a .…”
Section: Introductionmentioning
confidence: 99%
“…During the past two decades, chemically modified oligodeoxynucleotides (ODNs) have received much attention in the search for potential therapeutic and diagnostic agents and in the study of numerous biochemical and biological processes 15. To a great extent, these modifications have focused on replacing the phosphodiester group by phosphodiester mimics, such as phosphorothioate,6 methylphosphate,7 phosphoramidates,8 boranophosphate,9 alkylphosphotriesters,10 phosphorodithioate,11 phosphonomethyl,12 propynes,13 diene,14 phosphonoformate,15 and other groups 16. The phosphate‐modified ODNs have been used as inhibitors of gene expression,1 viral enzymes,2, 3 in vitro messenger‐RNA translation,4 and sequence‐specific DNA binding proteins 5…”
Section: Methodsmentioning
confidence: 99%